SOFTWARE DEVELOPMENT OF STEAM GENERATOR SYSTEM PERFORMANCE EVALUATION ASME PTC 4 2008 FOR CO-FIRING - Sawaddah, Calvin
Steam power plants in Indonesia have started implementing co-firing of coal and biomass. This co-firing is carried out to reduce the use of coal which is classified as not environmentally friendly because its combustion can produce CO2 gas emissions. Performance’s evaluation of steam generator was evaluated with the ASME PTC 4 Steam Generator 2008. However, the ASME PTC 4 can be used directly only for single firing.In this undergraduate thesis, the evaluation software for the ASME PTC 4 2008 steam generator system was developed for co-firing. In addition, this software is structured to make it easier for users to understand and use it. The development of software for evaluating performance of steam generator system is carried out using two methods, energy balance method and input-output method. Software validation is carried out by comparing the calculation results on software to sample calculation on ASME PTC 4 2008. Calculation simulation for co-firing is carried out using the modified PLTU Paiton Unit 1 400 MW 100 % load operation data. Modification is done by varying the fuel combination between coal and biomass with the types of empty fruit bunches of oil palm, rice husks, and wood with a percentage of 10% and 30% biomass. The result of this undergraduate thesis is in the form of a spreadsheet evaluation of a steam generator system for combined combustion. The validation of the calculation of the performance of the steam generator shows that the efficiency deviation in the energy balance method and the input-output method is 0.061 % and 0.139 %. For co-firing, the highest efficiency is obtained when using a combination of coal and empty fruit bunch of oil palm with a 30% biomass percentage with a value of 84,545 %.